IMPACT OF THE INABILITY TO BREASTFEED ON POST PARTUM DEPRESSION - Farah Milla Dwi Purwasari (Journal of Psychiatry Psychology and Behavioral Research, 2022)
Background: Depression is one of the major public health problems, which occurs twice as often in women than men during the fertile period. Depression or anxiety during pregnancy, stress from recent life events, a lack of social support, and a history of prior depression are all good predictors of postpartum depression. Providing expert breastfeeding support to women who plan to breastfeed is critical, as is providing caring support to women who want to breastfeed but are unable to do so. Objective: To determine women who have an inability to breastfeed that causes postpartum depression through the application of journal review descriptions. Methods: This review was carried out on case studies related to an inability to breastfeed and postpartum depression. The type of research is descriptive, which is a research method with the main objective of making an objective description or description of a situation. Results: The findings of this study's five case studies on the relationship between breastfeeding and postpartum depression were mixed. Regardless of the length of breastfeeding, EPDS scores showed a partial correlation that is substantially positively associated with physical stress, pain, lack of care, and pressure to quit from another person, even after adjusting for maternal age and education. Not exclusively breastfed, was twice as likely to develop postpartum depression. Conclusion: The inability to breastfeed due to difficulty and pain during breastfeeding is one of the reasons for the mother not to provide exclusive breastfeeding so that the mother cannot receive the psychological benefits of breastfeeding where the mother can increase the risk of postpartum depression.  Keywords: breastfeeding, postpartum depression.